Notarial Service of Extrajudicial Documents in the European Union: the Designation of Transmitting Agencies and its Communication to the Commission. The Choice of Means of Service Depending on its Effects - Gómez-Riesco Tabernero de Paz, Juan (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Regulation (EU) 2020/1784 provides for several means of service of documents without establishing a hierarchy between them, which in principle allows the notary to choose any of those. However, despite the notary’s competence in this matter in Spain, the lack of designation as ‘transmitting agency’ raises the question as to whether the notary can ‘directly’ effect service of extrajudicial documents through any of them. Likewise, the notary’s choice of the means of service may be affected by the effects that it has to produce in relation to the file or the right at stake, which the notary must assess on a case-by-case basis.